Preparation program of the youngest Top 100 tennis player: The training concepts and principles - Novak, D.; Felgate, D.; Podnar, H.; Vucetic, V. (Journal of Athletic Enhancement, 2013)
Conditioning preparation plays a key role in tennis. Typical microcyles and training session examples, together with main concepts and principles, are shown and explained in this paper. A very comprehensive array of anthropological and blood- producing system measures is also presented. Immediately after the preparation period, the young female tennis player achieved the greatest success in her career by playing in the finals of WTA tournament in Tashkent, Uzbekistan achieving the best placement in her career by becoming one of the world's top 100 female tennis players, and being the youngest one among them.